How not to stifle respondent's candour: establishing credibility & motivating individuals to repond during interviews / Radiah Othman, Jamaliah Said and Noraini Mohd Nasir - Othman, Radiah; Said, Jamaliah; Mohd Nasir, Noraini (Institute of Education Development (InED), 2007)
One method of collecting data is to interview respondents to obtain information on the issues of interest. Carrying out an inquiry involving humans and trying to obtain honest information from them is often a challenge to a researcher. Based from our experience in previous researches, the main aim of this paper is to provide practical insights and discusses general issues in interviewing together with the practicalities of carrying out types and styles of interview. Interviewees can bias the data when they do not express their true opinions thus, it is critical to establish rapport with the respondents and to motivate them to give responses and allaying whatever concerns they may have about the research and its consequences. We proposed that in order to profitably utilizing interviewing techniques, the interviewers must know how to start an interview, how to proceed with the questions, how to motivate respondents to answer, what to look for in the answers and how to close an interview. Researchers do not become good interviewers just by reading about it. Skills are involved which require practice. The tips provided in this paper should become a part of their repertoire for interviewing.